2019
DOI: 10.1002/bies.201800152
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Noncoding Mutations in Skin Cancers: UV Damage Susceptibility or Repair Inhibition as Primary Driver?

Abstract: Somatic mutations arising in human skin cancers are heterogeneously distributed across the genome, meaning that certain genomic regions (e.g., heterochromatin or transcription factor binding sites) have much higher mutation densities than others. Regional variations in mutation rates are typically not a consequence of selection, as the vast majority of somatic mutations in skin cancers are passenger mutations that do not promote cell growth or transformation. Instead, variations in DNA repair activity, due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 96 publications
(182 reference statements)
0
16
0
Order By: Relevance
“…Previous studies have indicated that decreased NER activity in regions of heterochromatin (Adar et al 2016;Roberts et al 2019) and near the central dyad axis of the nucleosome (Sabarinathan et al 2016;Brown et al 2018;Pich et al 2018) is associated with elevated somatic mutation rates in skin cancers. We wondered whether lower NER activity on the 3 ′ side of strongly positioned intragenic nucleosomes is associated with increased somatic mutation rates in UV-exposed cancers.…”
Section: Somatic Mutations In Human Melanomas Have An Asymmetric Distmentioning
confidence: 99%
“…Previous studies have indicated that decreased NER activity in regions of heterochromatin (Adar et al 2016;Roberts et al 2019) and near the central dyad axis of the nucleosome (Sabarinathan et al 2016;Brown et al 2018;Pich et al 2018) is associated with elevated somatic mutation rates in skin cancers. We wondered whether lower NER activity on the 3 ′ side of strongly positioned intragenic nucleosomes is associated with increased somatic mutation rates in UV-exposed cancers.…”
Section: Somatic Mutations In Human Melanomas Have An Asymmetric Distmentioning
confidence: 99%
“…In some cases, hot spot mutations in noncoding DNA promote carcinogenesis, as is the case for hot spot mutations in the promoter of the telomerase reverse transcriptase ( TERT ) gene (Horn et al, 2013; Huang et al, 2013; Chiba et al, 2017; Heidenreich & Kumar, 2017). However, recent studies have indicated that some hot spot mutations in noncoding DNA may not drive carcinogenesis, but instead function as neutral “passenger” mutations (Fredriksson et al, 2017; Buisson et al, 2019; Roberts et al, 2019). Such “passenger” hot spots are not under selection, but may instead arise from highly mutagenic processes, such as elevated UV damage formation, as occurs at the binding sites of ETS transcription factors (Elliott et al, 2018; Mao et al, 2018; Premi et al, 2019), or inhibition of repair (Poulos et al, 2016; Sabarinathan et al, 2016; Mao & Wyrick, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CPDs have been mapped across the genome at a resolution of 200 to 1,000 nt (5,6). Single-nucleotide measurements averaged over ETS family tran-scription factor binding motifs in many genes mutated in melanoma reveal that CPDs are elevated at these positions (21)(22)(23)). Yet the frequency of CPD induction at single-nucleotide resolution across the entire genome remains unknown, as do hotspots and tissue-dependence.…”
mentioning
confidence: 99%